Detection, identification and molecular characterization of phytoplasma associated with sesame phyllody and leafhopper in Delhi, India - Kumar, Pardeep; Celia Chalam, V; Boopathi, T; Parameswari, B; Ranebennur, Hemavati; Dubey, S C (Indian Journal of Plant Protection, 2024)
The phyllody symptomatic plants were found in sesame fields in Delhi (India) during Kharif 2018. A nested polymerase chain reaction using phytoplasma universal primers P1/P7 followed by R16F2n/R16R2 was used to detect phytoplasmas in symptomatic plants and leafhopper (Orosius albicinctus). The amplified 16S rDNA fragment was sequenced and BLAST analysis of 1.2-kb fragment confirmed the presence of phytoplasma in infected plants and leafhoppers. The virtual RFLP analysis of the amplified DNA fragments using 17 restriction enzymes showed that the detected phytoplasma belonged to the 16SrI-B group (Candidatus Phytoplasma asteris). The phylogenetic analysis showed that newly characterized isolate NBPGR-1 clustered with previously identified 16Sr I-B of sesame phyllody along with other 16Sr I-B group phytoplasma.